URGENSI FORMULASI DELIK KEKERASAN SEKSUAL BERBASIS GAMBAR DALAM UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK TERHADAP PEMULIHAN KORBAN SECARA YURIDIS - Yadi Ahmad Melyantoro; Rugun Romaida Hutabarat (Jurnal Hukum Adigama, 2022)
The rise of cases of spreading intimate photos containing sexual elements that are disseminatedwithout the consent or approval of one of the parties is a form of non-physical sexual violence,considering that sexual violence occurs because there is no consent or consent. New manifestations oftechnological advances make the realm of crime in cyberspace develop and sexual violence can occurnon-physically, one of which is image-based sexual violence. Therefore, the authors are interested inconducting an analysis of the phenomenon of image-based sexual violence in terms of the existing lawsin Indonesia with a comparison of laws in the UK. The research method used is normative legalresearch. From the research conducted, it is found that the ITE Law as a form of protection for victimsof image-based sexual violence that occurs in the virtual world is considered less effective because itdoes not provide a definition of violating decency in the virtual world and does not favor therestoration of the rights of victims of image-based sexual violence.